Advantages of Tailored Isotretinoin Treatment in Moderate to Severe Acne: Real-Life Data - Skroza, Nevena; Tolino, Ersilia; Balduzzi, Veronica; Bernardini, Nicoletta; Mambrin, Alessandra; Marchesiello, Anna; Marraffa, Federica; Rossi, Giovanni; Volpe, Salvatore; Proietti, Ilaria; Potenza, Concetta (Frontiers in Pharmacology, 2021)
This retrospective single center study analyzes efficacy and safety of isotretinoin for the treatment of moderate to severe acne in real-life clinical practice, particularly with regard to acne severity, isotretinoin cumulative dosage and patients’gender. Results suggest the opportunity of an early isotretinoin systemic treatment in patients affected by moderate acne and emphasize the importance of an appropriate dose adjustment in order to minimize adverse events.